ROLE OF TECHNICAL LEXICAL ANALYSIS IN DIDACTIC PROCESSES - Waldemar, LIB (Trends in education, 2010)
This article rise very important question concern becoming familiar with terminology belonging to particular scientific discipline by the students. Full capture of particular phrase by the student is taking place in the moment when he knows the specified notion, he can explain its meaning and he can use it in particular situation.By the point of view of the process connected with proper capture of scientific terminology there is very important assignment to be fulfil first of all properly regarding to linguistic and substantial teacher's statements, information contain in school textbooks and complementary elaborations for students in the form of lexicons, encyclopaedias and dictionaries.
Keywords: didactics; dictionary; lexicon; encyclopedia.